Associations between gabapentinoids and suicidal behaviour, unintentional overdoses, injuries, road traffic incidents, and violent crime: population based cohort study in Sweden - Molero,Y; Larsson,H; D'Onofrio,BM; Sharp,DJ; Fazel,S (BMJ, 2019)
OBJECTIVE: To examine associations between gabapentinoids and adverse outcomes related to coordination disturbances (head or body injuries, or both and road traffic incidents or offences), mental health (suicidal behaviour, unintentional overdoses), and criminality. DESIGN: Population based cohort study. SETTING: High quality prescription, patient, death, and crime registers, Sweden. PARTICIPANTS: 191 973 people from the Swedish Prescribed Drug Register who collected prescriptions for gabapentinoids (pregabalin or gabapentin) during 2006 to 2013. MAIN OUTCOME MEASURES: Primary outcomes were suicidal behaviour, unintentional overdoses, head/body injuries, road traffic incidents and offences, and arrests for violent crime. Stratified Cox proportional hazards regression was conducted comparing treatment periods with non-treatment periods within an individual. Participants served as their own control, thus accounting for time invariant factors (eg, genetic and historical factors), and reducing confounding by indication. Additional adjustments were made by age, sex, comorbidities, substance use, and use of other antiepileptics. RESULTS: During the study period, 10 026 (5.2%) participants were treated for suicidal behaviour or died from suicide, 17 144 (8.9%) experienced an unintentional overdose, 12 070 (6.3%) had a road traffic incident or offence, 70 522 (36.7%) presented with head/body injuries, and 7984 (4.1%) were arrested for a violent crime. In within-individual analyses, gabapentinoid treatment was associated with increased hazards of suicidal behaviour and deaths from suicide (age adjusted hazard ratio 1.26, 95% confidence interval 1.20 to 1.32), unintentional overdoses (1.24, 1.19 to 1.28), head/body injuries (1.22, 1.19 to 1.25), and road traffic incidents and offences (1.13, 1.06 to 1.20). Associations with arrests for violent crime were less clear (1.04, 0.98 to 1.11). When the drugs were examined separately, pregabalin was